(untitled) (Journal of Maternal and Child Health, 2016)
Background: The prevalence of exclusive breast feeding was 39.05% in Sukoharjo in 2015, which is far bellow the national target of 80%. A study has shown that massage oxytocin increases oxytocin (OT) hormone release, and eventually decreases adrenocorticotropin hormone (ACTH), nitric oxide (NO), and beta-endorphin (BE). This OT hormone release will increase milk ejection, which facilitate milk production. This study aimed to investigate the effect of breast care and oxytocin massages on breast milk production in post